Influences of healthcare workers' behaviours towards infection prevention and control practices in the clinical setting: A systematic review - Gift A. Mutsonziwa; Marwa Mojab; Megha Katuwal; Paul Glew (Wiley, 2024)
Abstract Aim To systematically evaluate empirical studies investigating the influences of healthcare workers' behaviours towards infection prevention and control practices in the Coronavirus clinical space, and to appraise and synthesise these findings. Design A systematic review of the literature. Methods The review used a five‐step framework described by Khan et al. (Journal of the Royal Society of Medicine, 2003, 96 and 118) of Framing questions for a review; Identifying relevant work; Assessing the quality of studies; Summarising the evidence; and Interpreting the findings. Searches were conducted in CINHAL, MEDLINE, PsychINFO, Scopus, and Google Scholar databases to retrieve relevant peer‐reviewed literature published in English between 2019 and 2023. Covidence and Joanna Briggs Quality appraisal tools were used for critical assessment. To improve transparent reporting, this review used a Synthesis Without Meta‐analysis (SWiM) in systematic review guidelines, as informed by Campbell et al. (BMJ, 2020, 368). Results Twenty studies were included in this review, identifying nine themes describing factors influencing HCWs' behaviours towards IPC practices in the coronavirus environment. The overarching influences emerged as knowledge‐oriented, person‐oriented, and environment‐oriented. Conclusion Healthcare workers' responsibilities at point‐of‐care involve providing direct care to patients with highly transmissible infections and working in clinical settings that may be ill‐designed for IPC practices, increasing the risk of transmission. Given the lack of a definitive solution to eradicate new mutant viruses and that IPC practices are the mainstay of prevention and control of transmissible, measures to improve are imperative. The identified HCWs' domains on behaviours towards IPC are critical in strategies to mitigate risks and further set an opportunity for developing an IPC model congruent with the rapid response required for HCWs during emerging or re‐merging mutant virus outbreaks. This is significant, given that HCWs' preparedness with IPC practices at point‐of‐care is central to patient care, the workforce and community safety.